2013
DOI: 10.1080/00028487.2012.734892
|View full text |Cite
|
Sign up to set email alerts
|

Landscape‐Scale Evaluation of Asymmetric Interactions between Brown Trout and Brook Trout Using Two‐Species Occupancy Models

Abstract: Predicting the distribution of native stream fishes is fundamental to the management and conservation of many species. Modeling species distributions often consists of quantifying relationships between species occurrence and abundance data at known locations with environmental data at those locations. However, it is well documented that native stream fish distributions can be altered as a result of asymmetric interactions between dominant exotic and subordinate native species. For example, the naturalized exot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 37 publications
7
52
1
Order By: Relevance
“…Our findings are consistent with the results of these previous studies in that the first PCA axis revealed that Brook Trout are associated with smaller streams at higher elevations (Table ), which often have more forest cover and colder instream temperatures (Wagner et al. ; DeWeber and Wagner ; Kanno et al. ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with the results of these previous studies in that the first PCA axis revealed that Brook Trout are associated with smaller streams at higher elevations (Table ), which often have more forest cover and colder instream temperatures (Wagner et al. ; DeWeber and Wagner ; Kanno et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…; Wagner et al. ), and maintaining groundwater upwelling zones that create thermal refugia (Hitt et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Wagner et al. ). Imperfect detection can affect model inferences and result in biased distribution estimates (Lahoz‐Monfort et al.…”
Section: Methodsmentioning
confidence: 98%
“…Introduction and establishment of non‐native salmonids (i.e., rainbow and brown trout) is further altering large‐scale brook trout distributions within the Chesapeake Bay watershed (Wagner et al. ).…”
Section: Methodsmentioning
confidence: 99%